Treatment Of Pseudo-Class III Malocclusions With The Han Appliance (2 Cases) - Tamer Türk; Selim Arıcı; Selim Çamaşuvi (Galenos Yayinevi, 1999)
A posturing forward of the mandible to clear anterior incisal interference brings forth a Pseudo Class III malocclusion. Early treatment of this type of problem prevents the development of a true Class III malocclusion. The establishment of normal incisor guidance induces a favorable occlusal relationship and sound growth of both jaws. In this case report the skeletal and dentoalveolar effects of the Han appliance on Pseudo Class III patients in the mixed dentition period were evaluated. 2 female cases aged 9 years 1 month and 11 years 9 month composed this case report. The Han appliance was worn for 4 months 10 days and 7 months 12 days. Skeletal and dentoalveolar changes were evaluated from pre- and post-treatment cephalograms. At the completion of treatment the following were observed: SNA angle increase and SNB angle decrease, anterior face height and lower anterior face height increase, overjet increase and overbite decrease. Treatment of Pseudo Class III malocclusions with the Han appliance induces an inhibition of mandibular growth along with a continuation of maxillary growth and an increase in the lower anterior face height, thus leading to the correction of the ANB angle. Increase in the overjet is mainly due to a protrusion of the upper incisors and a retrusion of the lower incisors; however, a slight skeletal contribution to this increase may be cited.